ANALISIS BIAYA SIKLUS HIDUP BANGUNAN: STUDI KASUS BIAYA AWAL, OPERASIONAL, DAN PEMELIHARAAN PADA KANTOR DESA NDORUREA 1 - kaidu, Triapriono; Chandra, Jimmy; Bhara, Firnimus Konstatinus; Soludale, Anastasia M.N. (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
This study sets out to analyze the total Life Cycle Cost (LCC) involved in constructing the Ndorurea 1 Village Office located in Nangapanda District, Ende Regency. Using the LCC approach, the research evaluates all expenses incurred throughout the building’s service life, which includes the initial construction costs, recurring annual operational costs, and scheduled maintenance costs over a span of 30 years. Data for this analysis were collected from the official Budget Plan (RAB), on-site observations, and interviews, and were processed using the Present Worth method. An inflation rate of 2.73% and a discount rate of 5.5% were applied to calculate the Future Value and convert it into Present Value. The findings reveal that the total LCC amounts to Rp 1,579,890,525.62, comprising an initial cost of Rp 784,461,207.31 (49.65%), operational costs of Rp 322,649,142.80 (20.42%), and maintenance costs of Rp 472,780,275.51 (28.92%). These results clearly show that more than half of the overall expenses are incurred after construction is completed. Hence, integrating the LCC approach from the initial planning stage is essential for ensuring cost efficiency, sustainability, and financial accountability in the development of village infrastructure.